Distinctive feature analysis of Telugu consonants - Umadevi R (Journal of All India Institute of Speech and Hearing, 1970)
Distinctive features which are the smallest units of language are defined to be the "physical and psychological realities of a phoneme (Singh, S.,1976)". The present study aimed at establishing a distinctive feature system of Telugu consonants. Four hundred and thirty word pairs were prepared using 31 Telugu consonants. These word pairs were prepared such that there was at least one feature difference between the two consonants of the word pair. Perceptual and Acoustical analysis were carried out to establish the features.